Dampak Wisata Religi Terhadap Ekonomi Sosial Masyarakat Lokal: (Studi Kasus Pada Makam Sapuro, Kota Pekalongan Barat) - Gunawan Aji; Frida Karima; Amelia Pramestika; Laila Safitri (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Religious tourism is one of the tours that is closely related to religion, history, customs, and beliefs of an individual or group. The existence of religious tourism in the midst of society has an economic and social impact on the surrounding community. The purpose of this study is to analyze the social economic impact on local communities with the existence of religious tourism Sapuro Tomb in West Pekalongan City. This research uses field research with a qualitative approach. The main data sources in this study are local communities and pilgrims. The results showed that there are economic and social impacts on local communities. The economic impact is felt by business people who are around Makan Sapuro, who get a large income every day because it is not uncommon for pilgrims to come from outside the city. The existing social impact is in the form of interaction of local people who work together if a religious event is held besides that there is interaction between the surrounding community with pilgrims or visiting worshipers.